FAKTOR-FAKTOR PSIKOLOGIS YANG MEMPENGARUHI PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH DASAR - Sakura Alwina; Sara Frimaulia (LPPM STKIP AL MAKSUM, 2026)
This study aims to determine the psychological factors that influence English learning in elementary schools. This study employs a qualitative approach using a literature review method. The data used in this study are secondary, derived from various published scientific articles. These sources include national and international journal articles and dissertations. The literature search was conducted through various scientific databases, such as Google Scholar, SINTA, Scopus, and Garuda. The data were analyzed using content analysis techniques. Furthermore, the data were grouped based on specific themes, such as learning motivation, anxiety in using English, self-confidence, self-efficacy, and learning interest. Based on the results of the literature review in this study, it is known that the success of English learning is influenced not only by students' academic abilities but also by their psychological condition and a supportive learning environment. The role of teachers in creating a positive learning atmosphere, providing motivation, and building students' self confidence are crucial factors in improving the quality of learning.